Direct determination of halogenated POPs in aqueous samples by in-tube SPME, focalization and GC-ECD analysis. Issue 14 (19th February 2015) - Russo, M. V.; Avino, P.; Veschetti, E.
<x xml:space="preserve">Abstract</x> A rapid analytical screening method allowing simultaneous analysis of few halogenated persistent organic pollutants (POPs) in water samples at ultra-trace levels was developed.